In the blood : understanding America's farm families - Wuthnow, Robert (Book collections on Project MUSE., 2015)
Farming is essential to the American economy and our daily lives, yet few of us have much contact with farmers except through the food we eat. Who are America's farmers? Why is farming important to them? How are they coping with dramatic changes to their way of life? In the Blood paints a vivid and moving portrait of America's farm families, shedding new light on their beliefs, values, and complicated relationship with the land. Drawing on more than two hundred in-depth interviews, Robert Wuthnow presents farmers in their own voices as they speak candidly about their family traditions, aspirations for their children, business arrangements, and conflicts with family members.